2008
DOI: 10.1139/l08-078
|View full text |Cite
|
Sign up to set email alerts
|

Internal curing of mortars by lightweight aggregates and its effects on hydration

Abstract: This study investigates the effects of lightweight aggregates (LWAs) on heat and degree of hydration in highstrength cementitious materials, in which natural pumice LWAs were used as water reservoirs to provide internal curing for mitigating autogenous deformation. Normal aggregates were substituted by LWAs at three different volume fractions, such as 8%, 16%, and 24% of total volume of mortars. The results show that as the amount of LWAs increased, the autogenous deformation significantly decreased, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
4
0
0
Order By: Relevance
“…Philleo [11] was the first to propose that pre-wetting porous aggregate can effectively reduce autogenous shrinkage. These findings were then confirmed by other researchers [7,20,21,24,26,52,[70][71][72][73][74][75][76]. Bentur et al [20] found that when the amount of fine LWA replacement for normal weight aggregate reached 25%, it could completely eliminate autogenous shrinkage of HPC, but Geiker et al [75] reported that value to be 20%.…”
Section: Autogenous Shrinkagesupporting
confidence: 56%
“…Philleo [11] was the first to propose that pre-wetting porous aggregate can effectively reduce autogenous shrinkage. These findings were then confirmed by other researchers [7,20,21,24,26,52,[70][71][72][73][74][75][76]. Bentur et al [20] found that when the amount of fine LWA replacement for normal weight aggregate reached 25%, it could completely eliminate autogenous shrinkage of HPC, but Geiker et al [75] reported that value to be 20%.…”
Section: Autogenous Shrinkagesupporting
confidence: 56%
“…The addition of prewetted LWAs delayed the time when the peak temperature was reached. A similar finding in previous work 62 suggests that the hydration heat increases slightly and the time to reach the maximum internal temperature (between 15 and 20 h) is longer as the proportion of LWAs increases.…”
Section: Influence Of Prewetted Lwas On Temperature Historysupporting
confidence: 90%
“…59,72 A similar finding was reported in previous work, 73 which suggests that adding presoaked LWAs into concrete can decrease the shrinkage and ensure the relatively more even distribution of shrinkage strain, particularly in concrete adding more presoaked LWAs. Another finding in previous work 62 also suggests that the autogenous shrinkage decreases significantly with an increasing volume of LWAs. Besides, the 14-day autogenous shrinkage reached 77.3%, 74.1%, 69.8%, and 49.2% of the 28-day autogenous shrinkage, suggesting that the autogenous shrinkage of concrete rose dramatically before 14 days and then the development rate became relatively steadily.…”
Section: Influence Of Prewetted Lwas On Shrinkagesupporting
confidence: 55%
“…The total water content is higher for compositions with recycled aggregate and is responsible of a higher cement hydration. Similar observations were already carried out when replacing natural aggregate by lightweight aggregate (Akcay and Tasdemir 2008) or when using super absorbent polymer (Wyrzykowski and Lura 2013).…”
Section: Temperature Evolution In Quasi-adiabatic Conditions and Heatsupporting
confidence: 78%